2002
DOI: 10.2308/aud.2002.21.2.39
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Decision Aid Orientation on Risk Factor Identification and Audit Test Planning

Abstract: In auditing, risk management involves identifying client facts or issues that may affect engagement risk, and planning evidence-gathering strategies accordingly. The purpose of this paper is to examine whether auditors' identification of risk factors and planning of audit tests is affected by decision aid orientation, i.e., a “negative” focus wherein client risk and its consequences are emphasized, or a “positive” focus where such factors are not emphasized. Specifically, we expect that auditors will identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 26 publications
3
40
0
1
Order By: Relevance
“…Our study contributes to the existing audit research literature on framing (e.g., Bedard and Graham 2002;Fukukawa and Mock 2011;Mock and Fukukawa 2016). First, our study extends this literature by showing that the framing of audit steps affects time budgets in the setting of fair-value auditing.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our study contributes to the existing audit research literature on framing (e.g., Bedard and Graham 2002;Fukukawa and Mock 2011;Mock and Fukukawa 2016). First, our study extends this literature by showing that the framing of audit steps affects time budgets in the setting of fair-value auditing.…”
Section: Introductionsupporting
confidence: 65%
“…4 Such compound manipulation is appropriate for some experiments but precludes the conclusion of which manipulated attribute is responsible for the framing effect. Bedard and Graham (2002;hereafter, BG) contribute to this research by suggesting that one of the reasons for the prior mixed results on frame effects could be attributed to weak frame manipulations. This explanation is consistent with the suggestion in psychology literature: attribute framing requires a manipulation that is strong enough to affect the encoding and representation of information relevant to the audit step (Levin and Gaeth 1988).…”
Section: Effect Of Step Frame On Audit Time Budgeting Judgmentsmentioning
confidence: 99%
“…Model ingatan memprediksi bahwa melalui pengalaman, individu membentuk struktur pengetahuan atau skema yang memberikan petunjuk lebih jauh mengenai informasi yang relevan terkait tugas (task-relevant information) (Bedard dan Graham, 2002). Data-data maupun informasi yang tersedia dalam audit seringkali berkonflik.…”
Section: Pengalaman Audit Dan Skeptisisme Profesional Auditorunclassified
“…Theoreticians of decision making have indicated that even experts have problem in assessing risks (Austen et al, 2000). In addition, many studies stated that the auditors' professional judgmental capability is limited, and they indicated that the auditors' professional judgment was affected by training, experience, and the capabilities dealing with time and complicated issues (Bedard & Graham, 2002;Helliar et al 1996;Khurana & Raman, 2004;Krishnan & Krishnan, 1997;Low, 2004;Turner et al 2002;Wustemann, 2004). These studies highlight the fuzzy nature of auditee risk assessment and qualitative and ambiguous attributes linked to risk assessment through traditional ARM.…”
Section: Introductionmentioning
confidence: 99%
“…There are different disadvantages on traditional auditing systems such as inefficient allocation resources for auditing program (Law, 2008;Helliar et al, 1996, Khorana & Raman, 2004Krishnan & Krishnan, 1997;Bedard & Graham, 2002;Mock et al, 1998). Auditing standards also require assessing audit risk in each independent audit engagement based on ARM (SAS.47;ISA.…”
Section: Introductionmentioning
confidence: 99%